Cash or food transfers paired with behavior change communication can reduce intimate partner violence even after transfers end - Roy, Shalini; Hidrobo, Melissa (2017)
Intimate partner violence (IPV) is widespread globally, with estimates showing that nearly 1 in 3 adult women worldwide have experienced some form of IPV. South Asia has among the highest regional rates in the world, with 41 percent prevalence of IPV. In Bangladesh, one survey found that 72.6 percent of married women reported experiencing violence at the hands of their husbands, and another showed that 74 percent of men reported inflicting violence on their wives. Violence against women in Bangladesh can be linked in part to strict observance of gender norms. Even though gender equality in the country has improved in some dimensions in recent decades, studies have found that patriarchal gender norms persist in much of rural Bangladesh. Purdah – the practice of female seclusion – is widely prevalent, and women’s movement outside the home continues to be restricted. Many women have little control over finances and limited social support, leading to reliance on their husbands and little bargaining power within their marriages.